Introduction of dynamic constitutive model into parallel computing system of strata motion and modeling of impact fracture process of roadway - Xuebin WANG; Qinjie ZHANG; Yishan PAN; Liqiang MA; Xiaoshuai LI; Dong LIU; Xueyuan BAI; Shuangyin CHEN (Meitan xuebao)
It is theoretically and practically significant to study the dynamic fracture of the roadway surrounding rock under impact for analyzing mechanisms of roadway rockbursts and for predicting and preventing them. When roadway rockbursts are modeled on the microcomputer, the foreign commercial software has small-scale computing capacity, low computing efficiency, and limited applicability. In the present paper, based on the GPU parallel computing system of the strata motion, i.e., StrataKing developed by us in the past ten years, the dynamic modeling ability is developed. The present method is validated through modeling the dynamic tests for rock specimens in uniaxial compression. The static constitutive model (the Hooke’s law) is replaced by the Zhu-Wang-Tang dynamic constitutive model applicable in a wide range of strain rates. The static cohesion in the Mohr-Coulomb criteria is replaced by the dynamic cohesion to consider the dynamic strength of rock. The local adaptive dumping leading to over damping in the dynamic modeling is replaced by the viscous dumping. The model composed of a roadway and its surrounding rock is impacted at the top of the model in the form of the constant velocity. Effects of the velocity on the instability of the model are investigated. At low strain rates, the instability of the model exhibits intermittent characteristics, which is due to the fact that the strength of the surrounding rock is low and few strain energy is stored. Thus, instability begins and ends easily, but no kinetic enough is provided for a serious large instability. However, at high strain rates, the development of the cracking regions at two sides of the roadway is very rapid, which is due to the fact that the need energy can be provided timely. Thus, the instability is continuous. When the stored strain energy is high, the instability takes place and ending is difficult, resulting in a serious dynamic hazard. The present work provides a good technical base for the study on the anti-impact of the roadway under support in the future.